The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1177/0194599813495372
|View full text |Cite
|
Sign up to set email alerts
|

Does Topical Anesthesia Using Aerosolized Lidocaine Inhibit the Superior Laryngeal Nerve Reflex?

Abstract: These findings indicate that preoperative topical lidocaine application may be helpful in attenuating airway-circulatory reflexes in laryngeal microscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…They found that lidocaine exaggerated findings associated with laryngomalacia and resulted in a higher laryngomalacia score, when compared to normal saline controls. However, Arslan et al demonstrated preserved laryngeal patency and closure in adults . Three studies reported that topical lidocaine reduced upper airway reflexes (cough, mechanoreceptor reflexes, and genioglossus muscle activity) during obstructive apnea and impaired the arousal response .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that lidocaine exaggerated findings associated with laryngomalacia and resulted in a higher laryngomalacia score, when compared to normal saline controls. However, Arslan et al demonstrated preserved laryngeal patency and closure in adults . Three studies reported that topical lidocaine reduced upper airway reflexes (cough, mechanoreceptor reflexes, and genioglossus muscle activity) during obstructive apnea and impaired the arousal response .…”
Section: Resultsmentioning
confidence: 99%
“…However, Arslan et al demonstrated preserved laryngeal patency and closure in adults. 7 Three studies reported that topical lidocaine reduced upper airway reflexes (cough, mechanoreceptor reflexes, and genioglossus muscle activity) during obstructive apnea and impaired the arousal response. [8][9][10] One study demonstrated that 4% lignocaine reduced upper airway reflex sensitivity for up to 100 minutes.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should still be noted that even brief gentle laryngoscopy and topical anesthesia can cause laryngospasm and subsequent airway collapse. [ 20 , 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Adult patients submitted to suspension laryngoscopy may also benefit from the use of vagolytic drugs at the beginning of the surgical procedure, especially from high vagal tone, identified in the cardiologic evaluation [9]. As another proposal, it is suggested that deep anesthesia associated with topical lidocaine may reduce the risk of asystole, but data are still limited [15].…”
Section: Discussionmentioning
confidence: 99%